if a={a, b},b={x, y},c={a, c, y} find (b-c)xa=(bxa)-(cxa)​

Question

if a={a, b},b={x, y},c={a, c, y} find (b-c)xa=(bxa)-(cxa)​

in progress 0
Mary 1 month 2021-08-17T22:08:41+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-17T22:09:56+00:00

    Step-by-step explanation:

    ( b-c ) = { x, y } – { a, c, y }

    ( b-c ) = {x}

    (b-c)×a = {x} × {a, b}

    = {(x,a) , (x,b)}

    Now,

    b×a= {x,y} × {a,b}

    = {(x,a) , (x,b) , (y,a) , (y,b)}

    c×a= {a,c,y} × {a,b}

    = {(a,a) , (a,b) , (c,a) , (c,b) , (y,a) , (y,b)}

    (b×a)-(c×a)= {(x,a) , (x,b) , (y,a) , (y,b)} – {(a,a) , (a,b) ,

    (c,a) , (c,b) , (y,a) , (y,b)}

    = {(x,a) , (x,b)}

    Therefore, (b-c)×a = (b×a)-(c×a)

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )